Rock This Way - Stanfill, Mel (University of Michigan Press, 2023)
Any and all songs are capable of being remixed. But not all remixes are treated equally. Rock This Way examines transformative musical works—cover songs, remixes, mash-ups, parodies, and soundalike songs—to discover what contemporary American culture sees as legitimate when it comes to making music that builds upon other songs. Through examples of how popular discussion talked about such songs between 2009 and 2018, Mel Stanfill uses a combination of discourse analysis and digital humanities methods to interrogate our broader understanding of transformative works and where they converge at the legal, economic, and cultural ownership levels.